1992
DOI: 10.1099/00207713-42-3-451
|View full text |Cite
|
Sign up to set email alerts
|

Flexibacter ovolyticus sp. nov., a Pathogen of Eggs and Larvae of Atlantic Halibut, Hippoglossus hippoglossus L.

Abstract: A psychrotrophic Ffexiibacter sp., Flexibacter ovolyticus sp. nov., was isolated from the adherent bacterial epiflora of Atlantic halibut (Hippoglossus hippoglossus L.) eggs and was shown to be an opportunistic pathogen for halibut eggs and larvae. The strains which we isolated had the enzymatic capacity to dissolve both the chorion and the zona radiata of the egg shells. A total of 35 isolates were characterized by using morphological and biochemical tests. These strains were rod shaped, gram negative, Kovacs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
89
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 39 publications
2
89
1
3
Order By: Relevance
“…nov.; 2, T. skagerrakense; 3, T. amylolyticum; 4, T. mesophilum; 5, T. ovolyticum; 6, T. maritimum. Data are from Wakabayashi et al (1986), Hansen et al (1992), Suzuki et al (2001), Frette et al (2004) and this study. +, Positive; 2, negative; W, weakly positive; V, variable reaction; ND, not determined; NG, no growth in the presence of NaCl only; n, number of strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…nov.; 2, T. skagerrakense; 3, T. amylolyticum; 4, T. mesophilum; 5, T. ovolyticum; 6, T. maritimum. Data are from Wakabayashi et al (1986), Hansen et al (1992), Suzuki et al (2001), Frette et al (2004) and this study. +, Positive; 2, negative; W, weakly positive; V, variable reaction; ND, not determined; NG, no growth in the presence of NaCl only; n, number of strains.…”
mentioning
confidence: 99%
“…The genus Tenacibaculum was proposed by reclassification of two species that had been assigned to the genus Flexibacter, Flexibacter maritimus (Wakabayashi et al, 1986) and Flexibacter ovolyticus (Hansen et al, 1992), as Tenacibaculum maritimum and Tenacibaculum ovolyticum, and with two novel species, Tenacibaculum mesophilum and Tenacibaculum amylolyticum (Suzuki et al, 2001). One further Tenacibaculum species, Tenacibaculum skagerrakense, has been described recently (Frette et al, 2004).…”
mentioning
confidence: 99%
“…Comparative 16S rRNA gene sequence analysis indicated that strain WJ-1 T formed a clade within the genus Tenacibaculum. The genus Tenacibaculum was first proposed by Suzuki et al (2001) to reclassify two species that had been assigned to the genus Flexibacter, Flexibacter maritimus (Wakabayashi et al, 1986) and Flexibacter ovolyticus (Hansen et al, 1992). At the time of writing the genus Tenacibaculum comprises 18 species (http://www.…”
mentioning
confidence: 99%
“…The genus Tenacibaculum, proposed by Suzuki et al (2001), belongs to the family Flavobacteriaceae (Reichenbach, 1992a, b;Bernardet et al, 1996Bernardet et al, , 2002 and currently comprises nine species: Tenacibaculum maritimum from diseased fish (Wakabayashi et al, 1986), T. ovolyticum from fish eggs (Hansen et al, 1992), T. amylolyticum from the surfaces of marine macroalgae and T. mesophilum from sponges (Suzuki et al, 2001), T. skagerrakense isolated from seawater (Frette et al, 2004), T. lutimaris, T. litoreum, T. aestuarii from tidal flat sediment (Yoon et al, 2005;Choi et al, 2006;Jung et al, 2006) and T. litopenaei isolated from a shrimp mariculture pond (Sheu et al, 2007).…”
mentioning
confidence: 99%